Community Critical Thinking Skills Framework: A Literature Review Study - Purwo Susongko; Rahul Bhandari; Mobinta Kusuma; Yuni Arfiani; Dika Pratama (Yayasan Keluarga Guru Mandiri, 2024)
Measuring one's thinking ability is very interesting because it relates to one's ability to understand the epistemology of science. Someone who can think critically will be able to distinguish between science and non-science and use scientific thinking to solve everyday problems. The ability to solve life's problems will impact a person's ability to solve health problems, economic issues, educational goals, and other practical problems. Indonesia must improve its World's Human Development Index (IPM) ranking. According to the UNDP (United Nations Development Programme), Indonesia has a Moderate HDI Score and was ranked 113th in the world in 2015. Furthermore, to improve the critical thinking skills of the community, several things need to be studied, including: (1) What are the constructs and standards of critical thinking skills that the community must master? (2) What is the critical thinking learning model for society? (3) What is the evaluation model for learning to think critically for society? This study aims to develop a framework for critical thinking skills that the community must master. This study uses a literature review research method with an integrative approach. There are two dimensions in the definition of significant critical thinking. First, critical thinking questions beliefs, statements, assumptions, trains of thought, actions, and experiences. The second fact of understanding critical thinking is the creative formulation of opinions or conclusions when faced with a question, problem, or issue.